Elaboration du chitosane à partir de la chitine de crevette rouge Aristeus antennatus (Risso, 1816) Appliqué à l’adsorption du Bleu de Méthylène - Cherguia, Samia; Mehdi, Hassiba (My University, 2019)
The application of shrimp and chitosan waste materials, which is a derivative of chitin as an adsorbent in the treatment of wastewater, has received considerable attention in recent years. The purpose of this study is to evaluate the adsorption capacity of the material obtained chitosan after the chemical treatments and which are: demineralization, and deproténisation, the discoloration and finally the deacetylation from the waste of the red shrimp Aristeus antennatus (Risso, 1816), fished in the Mostaganemoise region, according to a well-defined protocol for the removal of a dye of a type widely used in industry and in laboratories which is the Méthylène blue. We have studied the adsorption of Méthylène blue by the material prepared with shrimp powder with and without protein, we could not use the material of the chitosan obtained in the minimal amount obtained which is 5g per 100g initially used, for that we were interested in the material in the natural state that is to say to the chitin to study the effect of some parameters such as the time, the dose, the pH and the temperature. The Langmuir and Freundlich model and the B.E.T model were used to describe the nature of the adsorbent prepared in the laboratory. This adsorption is governed by the Freundlich model which reflects a heterogeneity of the adsorbent used and B.E.T which describes the nature of the second adsorbent and which multilayer nature. In conclusion, the materials prepared from protein-free and protein-free shrimp (Aristeus antennatus) have significant and encouraging adsorptive properties and the adsorption capacity (x / m) is of the order of 215 mg / L for shrimp-based material with protein and of the order of 194 mg / L for shrimp-based protein-free material. These materials prepared in the laboratory-based shrimp waste can be used for the removal of organic pollutants in replacement of commercial carbons whose cost remains very high.
Keywords: Red shrimp waste (Aristeus antennatus); Chitin; Chitosan; Méthylène blue; adsorption